Studi Inflasi Dan Stabilitas Nilai Mata Uang Dalam Ekonomi Islam - Henry Martin Adriansyah (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
Inflation is a financial phenomenon of major concern in a global context. From an Islamic perspective, the view of inflation is not merely economic but also encompasses profound moral and ethical dimensions. This study seeks to provide a comprehensive overview of inflation from an Islamic perspective, encompassing its definition, causes, impacts, and solutions in accordance with Islamic economic principles. Through a qualitative approach, including document and literature analysis, the concept of inflation in Islam and its implications for Muslim society are investigated. The discussion explores the causes of inflation from an Islamic perspective, including usury (interest), market instability, and unequal distribution of wealth. Furthermore, the impact of inflation on society, such as unfair redistribution of wealth and declining purchasing power, is analyzed. Finally, the study outlines proposed Islamic solutions to address inflation, such as regulating the financial system in accordance with Sharia law, controlling equitable production and distribution, and providing morally based economic education. With a deeper understanding of inflation from an Islamic perspective, it is hoped that the solutions implemented can address the problem of inflation effectively and fairly, in accordance with religious values.